2018
DOI: 10.1111/jog.13665
|View full text |Cite
|
Sign up to set email alerts
|

Compassion satisfaction, burnout and secondary traumatic stress among termination of pregnancy providers in two South African provinces

Abstract: Focusing on compassion satisfaction, burnout and secondary traumatic stress (STS) among termination of pregnancy (TOP) providers, a cross - sectional study was conducted among these providers in Gauteng and North West provinces of South Africa during 2014 and 2015. During 2014 and 2015, a cross-sectional study was conducted among TOP service providers in Gauteng and North West provinces. Consented providers completed a self-administered professional quality of life (PRoQOL) questionnaire, sociodemographic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
1
21
1
2
Order By: Relevance
“…About the total score for burnout syndrome, one study [36] reported medium levels, but two others [30,37] recorded low levels among gynecology and obstetrics nurses, with total mean scores of 29.9 and 6.19, respectively. The prevalence of burnout reported in these studies was 0.55% [28], 6.52% [34], 13.1% [33], and 21.4% [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About the total score for burnout syndrome, one study [36] reported medium levels, but two others [30,37] recorded low levels among gynecology and obstetrics nurses, with total mean scores of 29.9 and 6.19, respectively. The prevalence of burnout reported in these studies was 0.55% [28], 6.52% [34], 13.1% [33], and 21.4% [25].…”
Section: Resultsmentioning
confidence: 99%
“…The poor organization was related to higher levels of EE and D [25,28]. Another study [29] concluded that this problem results, fundamentally, in lower PA, while another found that low job satisfaction [36] is a major problem in this respect. Moreover, the gynecology and obstetrics service was reported to be among the units presenting the highest dropout rate in the nursing profession [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afrika'da yapılan bir çalışmada çoğunluğu hemşirelerden oluşan perinatoloji alanında çalışan sağlık bakım profesyonelleri arasında meslektaşlarıyla ilişkilerinden memnun ve uzman hemşirelerin şefkat memnuniyeti yüksek bulunmuştur. Aynı çalışmada sağlık bakım profesyonellerinde orta düzeyde tükenmişlik ve ikincil travmatik sendrom saptanmıştır (27). Avustralya'da fetal anomali riski taşıyan çiftlerle çalışan sağlık bakım profesyonellerinin çoğu iş çevresinin kendilerini, günlük yaşamlarını olumsuz etkilediğini, hasta sonuçları üzerinde kabus gördüklerini ve uykuya dalmakta zorlandıklarını bildirmişlerdir.…”
Section: Referanslarunclassified
“…ProQOL involves aspects of individual personal character, exposure to primary and secondary trauma in work settings and aspects of work environment (Stamm, ). Previous studies have been conducted in various work settings, including emergency departments and facilities for cancer nursing, psychiatric nursing, paediatric nursing, geriatric nursing and induced abortion care, which have helped our understanding of nurses’ ProQOL as a combination of associations between work environment and personal character (Galiana, Arena, Oliver, Sansó, & Benito, ; Kolthoff & Hickman, ; Mangoulia, Koukia, Alevizopoulos, Fildissis, & Katostaras, ; Mooney et al, ; Roney & Acri, ; Teffo, Levin, & Rispel, ; Wu, Singh‐Carlson, Odell, Reynolds, & Su, ). However, these studies did not focus on associations between ProQOL and the nurses’ own innate temperament.…”
Section: Introductionmentioning
confidence: 99%